Web and IoT-based hospital location determination with criteria weight analysis - Abeer Hadi; Mahmood Zaki Abdullah (Bulletin of Electrical Engineering and Informatics, 2022)
The hospital location selection for COVID-19-infected patients is out to be one of the most critical decisions for healthcare sectors in high-case countries. In this study, optimal urban hospital location selection for COVID-19-infected patients has been done out of multiple alternative locations in city of Baghdad Iraq by introducing a web application system that can find the best site from alternatives by using MEREC and modified technique for order of preference by similarity to ideal solution (TOPSIS) algorithms. MEREC algorithm is utilized to obtain criteria weights and modified TOPSIS for ranking the alternatives. Four criteria are considered with eight alternatives sites. The proposed system has two-part, hardware part (embedded systems) designed by utilizing NEO-6M GPS receiver with ESP8266NodeMCU to obtain coordinate of regions and then, using the HTTP protocol to communicate to submit these data to database server. The second part is the web application developed by PHP, JavaScript, CSS, HTML, and MySQL used to allow the system admin to enter the locations of the alternatives with their criteria into the system to get the best urban hospital location for COVID-19-patients. The results showed effectiveness of overall suggested system and appropriateness of the modified TOPSIS method over the traditional TOPSIS method in ranking the alternative.